Waste Disposal & Sustainable Energy - Wong, J.W.C.; Yan, Jian Hua.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer.)
Waste Disposal & Sustainable Energy (WDSE) is an international journal that publishes high-quality papers, communications, and discussion that advance waste disposal and sustainable energy technology. Acceptable article forms include original research article, review article, short communication, technical perspective and viewpoints. WDSE aims to promote research communication on waste disposal, renewable energy, and environment protection in the world. WDSE emphasizes the application of waste disposal and sustainable energy technology to environmental and earth issues. It provides a platform not only for basic research but also for industrial interests. We encourage scientists and researchers to submit papers that will advance our knowledge of waste disposal and highlight new approaches for waste disposal research and new technologies for pollution control. WDSE promotes cutting-edge studies of waste disposal science and state-of -art instrumentation to bridge the gap between basic science and industrial applications. WDSE accepts papers covering a broad range of waste disposal and sustainable energy related topics, including: waste generation, characterization, minimization, collection, treatment, and disposal, extending to environmental science, pollution research, environmental assessments, energy recovery, combustion optimization, clean and sustainable energy utilization.
Keywords: Renewable energy resources; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Waste management; Waste Management/Waste Technology; Renewable and Green Energy; Engineering Thermodynamics, Heat and Mass Transfer